Improving SINR 4G/LTE Femtocell in the Coexisting Network - Yaser, Muhammad (Jurnal Teknologi Elektro, 2023)
The coexisting of LTE femtocell with existing GSM network is proposed to address the challenge of limitation radio frequency spectrum.  SINR femtocells on coexisting networks are highly depend on conditions of distribution of femtocells, including the number and position of femtocells. On previous study have been extensively discussed coexistence of LTE femtocell integrated with GSM network. But it has not been discussed clearly how the strategy for increasing SINR femtocell in this coexisting network. In this study, various factors that affect SINR femtocell performance is analyzed mathematically. Simulation results show that SINR LTE femtocell increase about 0,2dB for every reduction of one femtocell deployed on the GSM network. When m = 2, SINR LTE femtocell reach 48.3dB then improve become 48.5dB when m=1. Meanwhile, when position of femtocell away from GSM base station from   x = 0.1R to x = R, SINR LTE femtocell increase about 2.5dB for a single femtocell on each GSM network. So as to increase SINR LTE femtocell can be done by reducing the number of femtocells deployed on GSM network and set LTE femtocell distribution patterns away from GSM base station.